2018
DOI: 10.1038/s41598-018-31716-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nickel/PA12 composite particles by defect-induced electroless plating for use in SLS processing

Abstract: In this work, Ni particles/PA12 powders (Ni/PA12) and graphite oxide (GO)-encapsulated Ni particles/PA12 powders (GO-Ni/PA12) composite powders were prepared by defect-included electroless plating technique, and its laser sintered behaviour was investigated. Results showed that a lot of defects could formed on the surface of CH3COOH etched PA12 powders. The defects would induce Ni and GO-Ni particles independently plated on the PA12 surface. Adding GO in the plating solution would facilitate the deposition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In Figure b, the five peaks at 2θ = 38.2, 44.4, 64.6, 77.4 and 81.6°, which are indexed to the (111), (200), (220), (311), and (222) planes of elemental silver, respectively . the characteristic peak (44.76°) is assigned to nickel plane (111), suggesting to the dominant nickel peak which is reported in the earlier literature …”
Section: Results and Discussionmentioning
confidence: 50%
“…In Figure b, the five peaks at 2θ = 38.2, 44.4, 64.6, 77.4 and 81.6°, which are indexed to the (111), (200), (220), (311), and (222) planes of elemental silver, respectively . the characteristic peak (44.76°) is assigned to nickel plane (111), suggesting to the dominant nickel peak which is reported in the earlier literature …”
Section: Results and Discussionmentioning
confidence: 50%
“…Huang et al [9], Wang et al [12] and Chang et al [8] found that the modified polyethylene terephthalate surface with -NH2 and -SH on its surface could absorb Ag particles, acting as catalytic center, so that the Cu coatings are deposited through REDOX reaction in the presence of catalytic centers. By far the most catalytic sites, such as metal particle (Ni [13], Cu [14], Pd [5] and Ag [9]), defect [15] and active group [16] has been reported. All of these, like Pd and Ag, are noble metals, meaning that they are excellent catalytic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] So far, this new technique has been mainly used to manufacture mechanical components in the automotive, aerospace, military and healthcare industries, as well as function materials in the environmental, biomedical, electrical and magnetic fields. [36][37][38][39][40][41][42] In the SLS process, voids may be formed when powder particles are sintered or melted rapidly by utilizing transient laser heating. When polymer particles and MOF fillers are mixed for SLS process, formed voids can provide MOF fillers embedded in the polymer matrix opening channels and increase the contact area between the fillers and the external ambient.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) printing is a disruptive innovative technology with high precision and controllability to manufacture macroscopic objects with complex shapes and geometries. Selective laser sintering (SLS) is one of the most important 3D printing techniques, by which a 3D solid matrix is built through the layer-by-layer sintering of hot-melt powdered material (including thermoplastic polymers, ceramics, and metals) using a program-controlled laser beam. So far, this new technique has been mainly used to manufacture mechanical components in the automotive, aerospace, military, and healthcare industries as well as functional materials for the environmental and biomedical applications. …”
Section: Introductionmentioning
confidence: 99%